Exploring the efficacy and safety of Ambroxol in Gaucher disease: an overview of clinical studies - Mohamed, Feda E.; Al-Jasmi, Fatma (Frontiers in Pharmacology, 2024)
Gaucher disease (GD) is mainly caused by glucocerebrosidase (GCase) enzyme deficiency due to genetic variations in the GBA1 gene leading to the toxic accumulation of sphingolipids in various organs, which causes symptoms such as anemia, thrombocytopenia, hepatosplenomegaly, and neurological manifestations. GD is clinically classified into the non-neuronopathic type 1, and the acute and chronic neuronopathic forms, types 2 and 3, respectively. In addition to the current approved GD medications, the repurposing of Ambroxol (ABX) has emerged as a prospective enzyme enhancement therapy option showing its potential to enhance mutated GCase activity and reduce glucosylceramide accumulation in GD-affected tissues of different GBA1 genotypes. The variability in response to ABX varies across different variants, highlighting the diversity in patients’ therapeutic outcomes. Its oral availability and safety profile make it an attractive option, particularly for patients with neurological manifestations. Clinical trials are essential to explore further ABX’s potential as a therapeutic medication for GD to encourage pharmaceutical companies’ investment in its development. This review highlights the potential of ABX as a pharmacological chaperone therapy for GD and stresses the importance of addressing response variability in clinical studies to improve the management of this rare and complex disorder.